To solve for e, you need to combine the like terms on both sides of the equation.
Starting with the left side of the equation:
9e + 4
Next, we can simplify the right side of the equation:
-5e + 14 + 13e
Combining the terms:
(9e + 4) = (-5e + 13e + 14)
Simplifying further, we combine the e terms:
9e + 4 = 8e + 14
To isolate the e term, we need to get rid of the constant terms. We subtract 4 from both sides:
9e = 8e + 10
Then, we subtract 8e from both sides:
9e - 8e = 8e + 10 - 8e
Simplifying the equation:
e = 10
Therefore, the solution to the equation is e = 10.
9e+4=-5e+14+13e
solve for e
1 answer